Measuring the impact of foreign capital flows in the Bahamian tourism industry - Demeritte, Kevin (1998)
Reviews the historical development of foreign capital inflows into the Bahamas and explores the impact that such flows have had on employment, and whether there have been associated benefits for the economy.